2018
DOI: 10.1016/j.molmet.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exercise intervention in obese pregnancy improves the cardiovascular health of the adult male offspring

Abstract: ObjectiveObesity during pregnancy is associated with an elevated risk of cardiovascular disease in the offspring. With increased numbers of women entering pregnancy overweight or obese, there is a requirement for targeted interventions to reduce disease risk in future generations. Using an established murine model of maternal obesity during pregnancy, we investigated if a treadmill exercise intervention in the mother could improve offspring cardiac health and explored potential underlying mechanisms.MethodsA 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 38 publications
6
53
0
2
Order By: Relevance
“…To our knowledge, no studies have reported on whether exercise during pregnancy can mitigate the adverse effects of maternal obesity on offspring vascular endothelial function. A recent study reported that maternal treadmill training can mitigate the adverse effects of maternal obesity on cardiac function in adult male C57BL/6J mouse offspring; vascular function was not assessed (Beeson et al, 2018). Taken together with our findings, exercise during pregnancy may be an effective nonpharmacological intervention to prevent adverse cardiovascular outcomes in offspring from mothers with gestational obesity.…”
Section: Discussionsupporting
confidence: 48%
“…To our knowledge, no studies have reported on whether exercise during pregnancy can mitigate the adverse effects of maternal obesity on offspring vascular endothelial function. A recent study reported that maternal treadmill training can mitigate the adverse effects of maternal obesity on cardiac function in adult male C57BL/6J mouse offspring; vascular function was not assessed (Beeson et al, 2018). Taken together with our findings, exercise during pregnancy may be an effective nonpharmacological intervention to prevent adverse cardiovascular outcomes in offspring from mothers with gestational obesity.…”
Section: Discussionsupporting
confidence: 48%
“…In line with the observed increased overall adiposity in both obese sedentary and exercised mice (Fernandez‐Twinn et al ; Beeson et al ), WAT mass expansion and fat deposition in liver, skeletal muscle and WAT was not significantly different in these two obese groups. This observation was also consistent with the maternal hyperleptinemia of both obese groups during pregnancy shown previously (Fernandez‐Twinn et al ).…”
Section: Discussionsupporting
confidence: 82%
“…The molecular changes induced by obesity alone and in response to exercising the obese dams were tissue specific and, in some instances, were related to alterations in maternal biochemical composition and concentrations of specific hormones and metabolites in late pregnancy. There were no beneficial effects of maternal exercise on the fetal growth restriction induced by maternal obesity despite the long term beneficial effects of the current exercise intervention in obese dams on cardiac (Beeson et al ) and metabolic health (Fernandez‐Twinn et al ) in adult offspring. Importantly this suggests that it is not fetal growth restriction per se that may mediate the long‐term detrimental health consequences of maternal obesity on the offspring (Fernandez‐Twinn et al ; Beeson et al ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations